Polymer-Clay nanocomposites with improved thermal and physical properties by free radical polymerization - Marwah Noori, Mohammed; Kamal, Yusoh; Jun Haslinda, Haji Shariffuddin (2018)
A huge interesting to use the Poly(N-vinylcaprolactam) (PNVCL) as thermoresponsive polymer in the biomedical applications, mainly in drug delivery systems. The Poly(N-vinylcaprolactam) (PNVCL) are show a lower critical solution temperature (LCST) as a temperature responsive polymers which ranging from 32 to 34ºC in aqueous solutions. In this study, free radical polymerization was used to polymerize the N-vinylcaprolactam (NVCL) with different types of the clay at 68ºC. For this purpose, Organo-modified C20, B30 and unmodified sodium montmorillonite clay (MMT) were employed to produce polymer/clay nanocomposite. Commercial grade C20, B30 and (MMT) were added in a range of 1-5 wt %, in wPP to prepare polymer-clay nanocomposites, following the free radical polymerization method. Fourier transform infrared spectroscopy (FTIR) was engaged to evaluate polymer structure before and after the polymerization [1]. Thermogravimetric analysis (TGA) was used to analyse the thermal stability and thermal properties for the polymer-clay nanocomposites. FTIR measurements as shown in Figure 1 confirmed the presence of clay (C20) in the nanocomposite produced in this study. The C-H stretch bond peaks in the range of 2852- 2936 cm-1 correspond to hydroxyl (C-H) group present on the surface of the composite. The band centered at ~1622 cm-1 represents the stretch mode of carboxylic group (C=O) [2, 3].